Computationally effective and accurate simulation of cyclic behaviour of old reinforced concrete columns. (15th October 2018) - Lee, Chang Seok; Han, Sang Whan
Highlights: A computationally efficient-accurate modeling procedure is developed for old RC columns. Empirical equations calculating model parameters are proposed. The proposed procedure is validated by comparing actual and simulated cyclic curves. Abstract: To evaluate the seismic performance of existing old reinforced concrete (RC) buildings, it is important to use an accurate analytical model. Most columns in these buildings do not satisfy the reinforcement details specified by current seismic design provisions. Columns that possess insufficient reinforcement details can exhibit significant pinching and cyclic deterioration in their strength and stiffness. They can also experience flexure-shear and shear failure during large earthquakes. The objective of this study is to simulate the cyclic behaviour of old RC columns accurately and efficiently with the Pinching4 model considering pinching and cyclic deterioration. Modelling parameters are calibrated based on the test results of 40 collected flexure-shear and shear critical columns. Columns failed by other failure modes rather than shear and flexure-shear failure are not considered in this study. Forward stepwise regression analyses are conducted to determine statistically significant variables from 34 candidate predictor variables and to propose the empirical equations of the modelling parameters. It is shown that the Pinching4 model with the proposed empirical equations accurately simulates the cyclic behaviour of both flexure-shear and shear-critical columns including pinching and cyclic deterioration in strength and stiffness.